Anatomical and Histological Study of Gills in Adult Mosquito Fish(Gambusiaaffinis) Baird and Girard - AL-Lehaibe, K. A.; AL-Mukhtar, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study showed that the branchial arch is characterized by the presence of irregular black line along its length. This line is condensations of melanocytes . The branchial arch bears two rows of gill rakers at its anterior (internal) side whereas its posterior (external) side bears two rows of gill filaments. Histologically, the gill arch is composed of hyaline cartilage surrounded by mixed bone ,which is covered by a mucous membrane. Its epithelium contains mucous cells and taste buds, whereas its loose connective tissue contains blood vessels and skeletal muscles. The histological structure of gill raker is similar to that of the gill arch except the absence of cartilage and muscles .The present study showed also that the gill filament epithelium is stratifiedcolumnar nearly and contains chloride cells ,mucous cells (goblet cells) and Rodlet cells .The secondary lamellae epithelium (respiratory epithelium ) is simple squamous epithelium. This epithelium surrounds the blood capillaries and the supporting pillar cells of the secondary lamella .